Parkia platycephala lectin enhances the antibiotic activity against multi-resistant bacterial strains and inhibits the development of Haemonchus contortus. (October 2019) - Silva, Romerio R.S.; Silva, Carolina R.; Santos, Valdenice F.; Barbosa, Cristina R.S.; Muniz, Debora F.; Santos, Ana L.E.; Santos, Maria H.C.; Rocha, Bruno A.M.; Batista, Karla L.R.; Costa-Júnior, Livio M.; Coutinho, Henrique D.M.; Teixeira, Claudener S.
Abstract: Lectins have been studied in the past few years as an alternative to inhibit the development of pathogenic bacteria and gastrointestinal nematodes of small ruminants. The development of new antibacterial and anthelmintic compounds is necessary owing to the increase in drug resistance among important pathogens. Therefore, this study aimed to evaluate the capacity of a glucose/mannose-binding lectin from Parkia platycephala seeds (PPL) to inhibit the development of Haemonchus contortus and to modulate antibiotic activity against multi-resistant bacterial strains, thereby confirming its efficacy when used in combination with gentamicin. PPL at the concentration of 1.2 mg/mL did not show inhibitory activity on H. contortus in the egg hatch test or the exsheathment assay. However, it did show significant inhibition of H. contortus larval development with an IC50 of 0.31 mg/mL. The minimum inhibitory concentration (MIC) obtained for PPL against all tested bacterial strains was not clinically relevant (MIC ≥ 1024 μg/mL). However, when PPL was combined with gentamicin, a significant increase in antibiotic activity was observed against S. aureus and E.coli multi-resistant strains. The inhibition of hemagglutinating activity by gentamicin (MIC = 50 mM) revealed that it may be interacting with the carbohydrate-binding site of PPL. It is this interaction between the antibiotic and lectin carbohydrate-binding site that may be responsible for the enhanced activity of gentamicin against multi-resistant strains. It can be concluded that PPL showed selective anthelmintic effect, inhibiting the development of H. contortus larvae and that it increased the effect of the antibiotic gentamicin against multi-resistant bacterial strains, thus constituting a potential therapeutic resource against resistant bacterial strains and H. contortus . Highlights: PPL showed selective anthelmintic effect, inhibiting the development of H. contortus larvae. PPL enhances the antibiotic activity against multi-resistant bacterial strains. PPL may be an alternative in the control of helminthes and multi-resistant strains.